1965
DOI: 10.1063/1.1714397
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Properties of Cobalt Oxide, Nickel Oxide, and Their Mixed Crystals

Abstract: Dielectric constant κ′, loss κ″, and conductivity σ of single crystals of CoO, NiO, and mixed crystals of CoO–NiO as a function of frequency from 102 to 1010 cps and temperature from −193°C to 400°C have been determined. The dielectric constant κ′ is constant (12.9 at 25°C) in the whole frequency range in CoO. It decreases with frequency in NiO and mixed crystals CoO–NiO. In NiO κ′ reaches a constant value (11.9 at 25°C) at 105 cps, and in CoO·NiO (12.3 at 25°C) at 1010 cps. The dielectric constants extrapolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
136
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 429 publications
(148 citation statements)
references
References 17 publications
10
136
2
Order By: Relevance
“…The temperature dependence of r opt can now be found by differentiating with respect to temperature: (15) The fact that ( ) is negative means that an increase in temperature will favour pitting by smaller anions, i.e. it agrees with the experimental observation that chloride becomes more aggressive than bromide at higher temperatures.…”
Section: Total Energysupporting
confidence: 67%
“…The temperature dependence of r opt can now be found by differentiating with respect to temperature: (15) The fact that ( ) is negative means that an increase in temperature will favour pitting by smaller anions, i.e. it agrees with the experimental observation that chloride becomes more aggressive than bromide at higher temperatures.…”
Section: Total Energysupporting
confidence: 67%
“…The measured dielectric constant, «′, is significantly reduced when the temperature is decreased because dielectric oscillators are thermally activated or when the frequency is increased ( Fig. 2A) because the space-charge polarization, which partially contributes to «′, is progressively suppressed at higher frequencies (33). Above T N , «′ is sensitive to the external magnetic field (B) at all selected frequencies, suggesting a strong magnetoelectric effect.…”
Section: Resultsmentioning
confidence: 86%
“…It is observed that the dielectric constant and dielectric loss decrease with increasing frequency and attain saturation at higher frequencies. The low dielectric constant value of the crystal at high frequency is attributed to space charge polarization [25]. The very high value of dielectric constant at low frequencies is due to the presence of ionic, electronic and orientation polarizations.…”
Section: Dielectric and Thermal Analysesmentioning
confidence: 99%